EFEKTIVITAS PEMBERIAN BACK EXERCISE TERHADAP PENGURANGAN SKALA NYERI PADA PENDERITA NYERI PUNGGUNG BAWAH PENSIUNAN PEKERJA DI RUMAH SAKIT DIAN HARAPAN JAYAPURA - Indra Gustab Purba; Jhon Robi Purba (Indonesian Trust Nursing Journal, 2023)
Work position, obesity and family history of musculoskeletal disorder sufferers. Other factors that influence the incidence of low back pain include individual characteristics, namely body mass index (BMI), height, exercise habits, length of work, work position and weight of workload. Excessive weight and obesity are associated with an increase in the prevalence of low back pain. The purpose of this researcher aims to determine the Effect of the Effectiveness of Back Exercise Administration on reducing the scale of pain in retired Lower Back Pain sufferers in the hospital in Jayapura. This research method is a type of Experimental research. The research design that will be used is a one-group pre-test and post-test design to see the effectiveness of giving back pain back exercise for retirees at Dian Harapan Hospital, Jayapura. Results Of the 12 subjects of the study, 5 people (41.7%) were women and 7 people (58.3%) were men, Of the total participants had a vulnerable age of 55 - 75 years, age range of 55 -65 years as many as 6 people (50%), and 66 - 75 there were 6 people (50%) with an average and standard deviation of 65.92±4.92 retired civil servant teachers as many as 5 people (41.7%), private pensioners and retired offices of 2 people each (16.7) and retired TNI, PLN and BUMN each as many as 1 person (8.3%). Conclusion The provision of Back Exercise has an effect on reducing the scale of pain in retired Lower Back Pain sufferers at Dian Harapan Jayapura Hospital. And Back Exercise can reduce pain in Retired Lower Back Pain patients at Dian Harapan Hospital Jayapura. Abstrak Posisi kerja,kegemukan dan riwayat penyakit keluarga penderita musculoskeletal disorder. Faktor lain yang mempengaruhi kejadian nyeri punggung bawah meliputi karakteristik individu yaitu indeks masa tubuh (IMT), tinggi badan, kebiasaan olahraga, masa kerja, posisi kerja dan berat beban kerja. Berat badan berlebihan dan obesitas berhubungan dengan kenaikan prevalensi nyeri punggung bawah. Tujuan peneliti ini bertujuan Untuk mengetahui Pengaruh Efektivitas Pemberian Back Exercise terhadap pengurangan skala nyeri pada penderita Nyeri Punggung Bawah Pensiunan Di rumah sakit dian harapan Jayapura. Metode penelitian ini merupakan jenis penelitian Eksperimental. Rancangan penelitian yang akan digunakan adalah one group pre-test and post-test design untuk melihat efektivitas pemberian back exercise nyeri punggung bawah pensiunan di Rumah sakit Dian Harapan Jayapura. Hasil Dari 12 subjek penelitian, 5 orang (41,7%) adalah perempuan dan 7 orang (58,3%) adalah laki-laki, Dari keseluruhan peserta memiliki rentan usia 55 – 75 tahun, Rentang usia 55 -65 tahun sebanyak 6 orang (50%), dan 66 – 75 terdapat 6 orang (50%) dengan rata-rata dan standart deviasi 65,92±4,92.pensiunan PNS Guru sebanyak 5 orang (41,7%), Pensiunan Swasta dan pensiunan Kantor masing-masing sebanyak 2 orang (16,7) dan Pensiunan TNI, PLN dan BUMN masing – masing sebanyak 1 orang (8,3%). Kesimpulan Pemberian Back Exercise efektik terhadap pengurangan skala nyeri pada penderita Nyeri Punggung Bawah Pensiunan Pekerja Di Rumah Sakit Dian Harapan Jayapura. Dan Latihan Back Exercise dapat mengurangi nyeri pada pasien Nyeri Punggung Bawah Pensiunan pekerja Di Rumah Sakit Dian Harapan Jayapura.